Association of periodic fasting lifestyles with survival and incident major adverse cardiovascular events in patients undergoing cardiac catheterization. (6th November 2020) - Bartholomew, Ciera L; Muhlestein, Joseph B; Anderson, Jeffrey L; May, Heidi T; Knowlton, Kirk U; Bair, Tami L; Le, Viet T; Bailey, Bruce W; Horne, Benjamin D
Abstract: Aims: Animal models repeatedly show fasting increases longevity. Human data, though, are limited to anecdotal claims. This study evaluated the association of routine fasting with survival and, secondarily, with incident major adverse cardiovascular events. Methods and results: Cardiac catheterization patients enrolled in the Intermountain INSPIRE longitudinal cohort ( n  = 2785) during 2013–2015 were followed through March 2019. A fasting survey was completed in n  = 2025 (73%) of this cohort and 1957 were included in the final data analysis after 68 participants were removed (24 for data issues and 44 for fasting less than 5 years). Self-reported routine fasting behaviour, years of participation in fasting, and other fasting characteristics were surveyed. Mortality was the primary outcome and incident myocardial infarction (MI), stroke, and heart failure (HF) were secondary. Routine fasters ( n  = 389, mean age 64 ± 14 years, 34% female) averaged 42 ± 18 years of routine fasting (minimum 5 years). Non-fasters ( n  = 1568, aged 63 ± 14 years, 36% female) included never fasters ( n  = 1120 with 0 years of fasting) and previous fasters ( n  = 448 who averaged 32 ± 21 years of prior fasting but had stopped prior to enrolment). Routine fasters had greater survival vs. non-fasters [adjusted hazard ratio (HR) = 0.54, 95% confidence interval (CI) = 0.36–0.80; P  = 0.002] and lower incidence of HF (adjusted HR = 0.31, CI = 0.12–0.78; P  = 0.013), but not MI or stroke after adjustment. Conclusions: Routine fasting followed during two-thirds of the lifespan was associated with higher survival after cardiac catheterization. This may in part be explained by an association of routine fasting with a lower incidence of HF. Clinical study registration: The Intermountain INSPIRE registry https://clinicaltrials.gov/, NCT02450006.